Science (and) Fiction in Ballard’s Vermilion Sands (Altre Modernità, 2020)
Science, technology, and the (futuristic and surreal) uses of them are undoubtably essential elements in Ballard’s writing. His scientific language is both very elaborate and refined. Sometimes, it attains a metafictional mode, while it allows for an accurate discourse on (New Wave) science fiction, art, and narration. In Vermilion Sands, a collection of short stories published in 1971, Ballard describes this overlit place as an exotic suburb of the mind, and of the future. In Vermilion Sands, trauma flowers, singing plants, non-aural music, sound jewelry, automated poetry machines, sonic sculptures, self-painting canvasses, psychotropic houses are the psychological drives in these macabre, grotesque, and strange psychodramas. In this paper, I will analyze how science and technology contribute to build neural landscapes through a metanarrative perspective in Vermilion Sands.